The significance of prey avoidance behavior for the maintenance of a predator color polymorphism. (17th October 2018) - Ajuria Ibarra, Helena; Kinahan, Michael; Marcetteau, Julien; Mehigan, Andrew J R; Ziegelmeier, Ross O; Reader, Tom
Abstract : Why do some animals have variable color patterns? We show that honeybee behavior can favor the persistence of red, yellow and white patterns in spider predators. Although it is well known that predators can promote morphological diversity in their prey, our study is one of the first to show that the reverse might also happen. Our results add to our understanding of the ecological processes shaping the appearance of animals in natural populations. Abstract: The existence of conspicuous color polymorphisms in animals provides an ideal opportunity to examine the mechanisms which determine genetic and phenotypic variation in populations. It is well known that directional and negative frequency-dependent selection by predators can influence the persistence of color polymorphisms in their prey, but much less attention has been paid to the idea that prey behavior could generate selection on predator color morphs. In this study, we examine the role that avoidance behavior by honeybees might play in selection on a color-polymorphic sit-and-wait predator, the crab spider Synema globosum . In 2 field experiments, we offered flowers harboring spiders of different color morphs to foraging honeybees. In the first, we tested for a preexisting propensity in honeybees to avoid one spider morph over another, and whether this behavior is influenced by the flower species on which spiders hunt. In the second, we tested the ability of bees to learn to avoid spider morphs associated with a previous simulated attack. Our results suggest that honeybees do not impose strong directional selection on spider morphs in our study population, and that avoidance behavior is not influenced by flower species. However, we find evidence that honeybees learn to avoid spiders of a color morph that has previously been associated with a simulated attack. These findings are the first empirical evidence for a mechanism by which prey behavior might generate negative frequency-dependent selection on predator color morphs, and hence potentially influence the long-term persistence of genetic and phenotypic diversity in predator populations.